Labor in the tourism and hospitality industry : skills, ethics, issues, and rights - Elshaer, Abdallah M.; Marzouk, Asmaa M. (Oakville, ON ; Palm Bay, Florida : Apple Academic Press, 2019)
"An organization's workforce is arguably the greatest asset of any organization, and the tourism and hospitality is an extremely labor-intensive industry. It is heavily dependent on the human factor to ensure delivery and quality products and services. This volume, Labor in the Tourism and Hospitality Industry: Skills, Ethics, Issues, and Rights, takes an in-depth look at workforce issues in the tourism and hospitality industry, focusing on labor skills, ethics, rights, and more. It examines manpower planning beyond forecasting estimates to include investigative techniques in a way that offers insight for economic planning in both tourism and tourism education. It also specifically covers the importance of ethics in the workplace and labor rights. The authors use economic, sociological, and psychological analysis and take a pragmatic stance on the challenges of the workforce. The authors look at the specifics of the labor market of the tourism and hospitality industry, discussing the current status of the industry's organizations and how they are suffering labor shortages (qualitative or quantitative) and constant turnover--resulting in significant costs to organizations. Research has found that to labor shortages and turnover coincide with HRM policies and practices that seem to ignore the labor rights of workers. Topics such as low wages and overdependence on tipping, workforce diversity, technological change resistance, employee turnover, seasonality issues, and more are examined. The volume also provides a section on labor rights in the tourism and hospitality industry, which looks at labor trafficking and issues in social justice, human rights, and labor rights. The volume offers readers, whether they are students, managers, planners, or educationalists, an in-depth understanding of tourism employment as a whole and in its specifics. It provides managers and employers with an understanding of the human resource management skills they must cultivate. Additionally, professional senior human resources practitioners in the tourism industries will benefit from the holistic view of the labor market."--
The significance of the tourism and hospitality industry in employment creation -- A critical analysis of labor supply and demand in the tourism and hospitality industries -- Labor skills and training in the tourism and hospitality industry -- Labor shortage in the tourism and hospitality industry -- Ethics in the tourism and hospitality industry -- Labor ethics and social responsibility in the tourism and hospitality industry -- Labor turnover in the tourism and hospitality industry -- Tourism and seasonality -- The high vulnerability of the tourism industry to risks and emergencies -- Low wages and overdependence on tipping -- Workforce diversity in the tourism and hospitality industry -- Technological change resistance -- Labor discrimination -- Labor trafficking in the tourism and hospitality industry -- Social justice, human rights, and labor rights.
OCLC-licensed vendor bibliographic record.
Keywords: Tourism -- Employees -- Supply and demand; Hospitality industry -- Employees -- Supply and demand; Labor turnover; Employee rights; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Labor; BUSINESS & ECONOMICS / Industries / Hospitality, Travel & Tourism